2016
DOI: 10.1177/0003702816648965
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Breakdown Spectroscopy (LIBS) in a Novel Molten Salt Aerosol System

Abstract: In the pyrochemical separation of used nuclear fuel (UNF), fission product, rare earth, and actinide chlorides accumulate in the molten salt electrolyte over time. Measuring this salt composition in near real-time is advantageous for operational efficiency, material accountability, and nuclear safeguards. Laser-induced breakdown spectroscopy (LIBS) has been proposed and demonstrated as a potential analytical approach for molten LiCl-KCl salts. However, all the studies conducted to date have used a static surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…In this work, the aerosol-LIBS system used in previous molten salt studies was implemented and a full description of the system can be found in the literature. 21,22 In brief, the system consists of a stainless-steel Collison nebulizer, a sealed sampling chamber (with sapphire windows), and a series of filters to remove the aerosol from the gas stream as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the aerosol-LIBS system used in previous molten salt studies was implemented and a full description of the system can be found in the literature. 21,22 In brief, the system consists of a stainless-steel Collison nebulizer, a sealed sampling chamber (with sapphire windows), and a series of filters to remove the aerosol from the gas stream as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a novel molten salt aerosol approach has been demonstrated using Ce. 21,22 In this approach, a nebulizer with an argon gas carrier was used to generate a molten salt aerosol into which the laser light was focused to create the plasma. The advantages of this system are that splashing is reduced and the optics are isolated from the salt system.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-induced breakdown spectroscopy was first proposed for electrochemical sampling measurements because it can be performed at significant distance from its intended target, potentially simplifying its implementation and potentially allowing for deployment above the electrorefiner vessel. [62][63][64][65] LIBS has been considered for both in situ 63 and ex situ 65 deployment. The deployment scenario would drive latency of measurement (low for in situ measurements and medium to high for ex situ).…”
Section: Iiib2 Laser-induced Breakdown Spectroscopymentioning
confidence: 99%
“…There are some examples of the practical application of LIBS to characterize materials specifically from the nuclear arena in published literature. To date, the successful identification of fission products, actinides, radionuclides, and activated corrosion products has been reported within a range of supporting materials that include mixed oxide fuels [29], vitrified high level waste [30], and molten salt electrolytes [31]. These include the use of LIBS to analyse specific radioactive materials such as uranium or plutonium, and radionuclides such as 90 In this new study, we undertake a range of LIBS analyses to explore the use of multivariate statistical analysis techniques for discriminating between graphite and charcoal, which is used to represent other carbon-bearing materials and represents a challenging test case.…”
Section: Minor Comments 55mentioning
confidence: 99%